Jobs and Civil Rights The Role of the Federal Government in Promoting Equal Opportunity in Employment and Training. Clearinghouse Publication No. 16 - Nathan, Richard P.; Brookings Institution, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
In order to assess their effect on job inequality in private employment, a study was made of Title VII of the Civil Rights Act of 1964, Executive Order 11246, and federally aided employment service and job preparation programs with equal employment opportunity as an objective. Altogether, 250 interviews were conducted with federal officials responsible for administering the programs and with directors in selected metropolitan areas. In addition, questionnaires concerning experience in equal employment opportunity programs were mailed to 102 selected State and local civil rights leaders and 35 were returned. Some major conclusions and recommendations include: (1) While the Equal Employment Opportunity Commission is beginning to control some of its problems, the commission needs to increase its effectiveness by moving away from individual cases to broader self-starting activities, (2) More determined application of sanctions under Executive Order 11246 is imperative if the program is to be effective and respected, and (3) Closer linkages should be established between the equal job enforcement and manpower programs. (SB)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (CR1.10:16, $2.50).
Sponsoring Agency: Commission on Civil Rights, Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Employment Opportunities; Federal Legislation; Training; Civil Rights; Equal Opportunities (Jobs); Federal Programs; Labor Force Development; Labor Utilization; Civil Rights Act 1964 Title VII -- Equal Employment Opportunity Commission -- Executive Order 11246